Bira Beach Tourism Governance Through Digital Marketing Communication Strategies - Kamsar, Kamsar; Alim, Irwan; Akbar, Muhammad Randhy; Mone, Ansyari (Universitas Muhammadiyah Makassar, 2023)
This research delves into the role and implications of digital marketing communication strategies in the tourism governance of Bira Beach. Bira Beach, renowned for its pristine coastal beauty, has witnessed fluctuating tourism trends over the years. Ensuring sustainable tourism development, which balances economic benefits, environmental protection, and socio-cultural integration, necessitates effective governance mechanisms. Digital marketing communication strategies have emerged as instrumental in shaping this governance. Through a qualitative approach encompassing interviews, surveys, and digital data analytics, this study explores (1) the existing digital communication practices in promoting Bira Beach, (2) stakeholders' perceptions about the effectiveness of these practices, and (3) the influence of these strategies on tourism governance frameworks and decisions. Preliminary findings suggest that well-structured digital communication campaigns can enhance stakeholder participation, foster transparent decision-making, and drive sustainable tourism policies. However, certain challenges like digital literacy, infrastructural constraints, and authenticity concerns have been identified. The research emphasizes the need for a cohesive strategy that integrates technology, local community insights, and environmental considerations for robust tourism governance at Bira Beach. This study contributes to the growing body of knowledge on the intertwining realms of digital marketing and tourism governance, offering insights for policy-makers, tourism planners, and marketers.